2020
DOI: 10.1136/flgastro-2020-101701
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on key performance indicators in pancreatobiliary endoscopy: prioritise, minimise risk, keep scoping and training

Abstract: BackgroundThe COVID-19 pandemic has profoundly affected endoscopy services including pancreatobiliary (PB) endoscopy across the UK. The British Society of Gastroenterology and Joint Advisory Group have issued guidance for managing endoscopy services safely throughout this period. There have been perceived concerns among the PB endoscopists that wearing full personal protective equipment might have an adverse impact on key performance indicators (KPIs) in endoscopic retrograde cholangiopancreatography (ERCP) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…During the pandemic era, especially the lockdown period, many previous studies reported a reduction in cases of endoscopic procedure including upper gastrointestinal endoscopy, colonoscopy, and endoscopic ultrasound. The reduction of elective endoscopic procedures was found to have led to the reduction in the malignancy detection rates, 17 , 18 which may have delayed diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic era, especially the lockdown period, many previous studies reported a reduction in cases of endoscopic procedure including upper gastrointestinal endoscopy, colonoscopy, and endoscopic ultrasound. The reduction of elective endoscopic procedures was found to have led to the reduction in the malignancy detection rates, 17 , 18 which may have delayed diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…One of the first studies to assess the impact of COVID-19 on KPIs [44], analyzed the impact of COVID-19 on pancreato-biliary endoscopy-related KPIs. However, limited research was found to assess the HCOs -related KPIs at COVID-19 in general.…”
Section: Kpis During Covid-19 Pandemicmentioning
confidence: 99%